Sonic hedgehog improves redifferentiation of dedifferentiated chondrocytes for articular cartilage repair. - Lin Lin (Public Library of Science (PLoS), 2014)
Sonic hedgehog (Shh) is involved in the induction of early cartilaginous differentiation of mesenchymal cells in the limb. We investigated whether Shh could promote redifferentiation of dedifferentiated chondrocytes and have a favorable effect on the regeneration of cartilage. Articular chondrocytes of rats were separated and cultured. The redifferentiation of dedifferentiated chondrocytes transfected with Shh was evaluated using monolayer and pellet culture system. The signaling molecules (Ptc 1, Gli 1 and Sox9) of the hedgehog pathway were investigated. A rat model of articular cartilage defect was used to evaluate cartilage repair after transplantation with dedifferentiated chondrocytes. After Shh gene transfer, the hedgehog pathway was upregulated in dedifferentiated chondrocytes. Real time-PCR and western blot analysis verified the stronger expression of Ptc1, Gli1 and Sox9 in Shh transfected cells. Shh upregulates the Shh signaling pathway and multiple cytokines (bone morphogenetic protein 2 and insulin-like growth factor 1) in dedifferentiated chondrocytes. After transplantation in the joint, histologic analysis of the regenerative tissues revealed that significantly better cartilage repair in rats transplanted with Shh transfected cells. These data suggest that Shh could induce redifferentiation of dedifferentiated chondrocytes through up-regulating Shh signaling pathway, and have considerable therapeutic potential in cartilage repair.